2020
DOI: 10.1063/5.0010628
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio quantum dynamics of charge carriers in graphitic carbon nitride nanosheets

Abstract: Graphitic carbon nitride (g-C3N4), a metal-free and visible light responsive photocatalyst, has garnered much attention due to its wide range of applications. In order to elucidate the role of dimensionality on the properties of photo-generated charge carriers, we apply nonadiabatic (NA) molecular dynamics combined with time-domain density functional theory to investigate nonradiative relaxation of hot electrons and holes, and electron–hole recombination in monolayer and bulk g-C3N4. The nonradiative charge re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 93 publications
5
47
3
Order By: Relevance
“…Recently, Prezhdo and co-workers discussed the charge carrier dynamics in monolayer g-C 3 N 4 using NAMD. [38] Their results showed that due to the significant orbital overlap, the photoexcited electrons in the higher conduction band orbitals will relax to the bottom of the conduction band in 100 to 200 fs which is close to our results attributed to the interlayer interaction. Ultrafast interlayer charge transfer and good spatial separation in the twisted bilayer system imply a potential enhancement in photocatalytic performance.…”
Section: Resultssupporting
confidence: 91%
“…Recently, Prezhdo and co-workers discussed the charge carrier dynamics in monolayer g-C 3 N 4 using NAMD. [38] Their results showed that due to the significant orbital overlap, the photoexcited electrons in the higher conduction band orbitals will relax to the bottom of the conduction band in 100 to 200 fs which is close to our results attributed to the interlayer interaction. Ultrafast interlayer charge transfer and good spatial separation in the twisted bilayer system imply a potential enhancement in photocatalytic performance.…”
Section: Resultssupporting
confidence: 91%
“…Nanosheets of 1-2 layers, [50,165] few layers, [166,167] and 6-12 layers have been previously studied, [49,75] and monolayers have been modeled using first-principle calculations. [168][169][170] However, these sporadic reports do not provide a clear picture of how the thickness of nanosheets affects their properties. In 2D transition metal dichalcogenides with thicknesses of one to several layers, exciton consideration is of great significance to exploit these materials in high-end photonic and plasmonic applications.…”
Section: Perspectivementioning
confidence: 99%
“…[171] In the case of 2D perovskites, sample thickness can have a profound effect on exciton-exciton annihilation. [172] Current knowledge indicates that the charge carrier dynamics of monolayer g-CN is very different from that of bulk CN, [169] suggesting that corrugation has a significant influence on g-CN properties (bandgap and optical absorption) and thus influences optoelectronic and catalytic performance, [170,173] as in the case of graphene. [174] Some other interesting aspects of g-CN also deserve a closer look.…”
Section: Perspectivementioning
confidence: 99%
“…Depending on the level of theory used and the size of the systems studied, such calculations may be quite expensive. Conventionally, few-picosecond trajectories are computed for systems of few hundreds of atoms while using Kohn–Sham (KS) orbitals and pure functionals such as the Perdew–Burke–Ernzerhof (PBE). ,, Recently, we have extended this procedure to go beyond the KS picture via the time-dependent density functional theory (TD-DFT) calculations of excited states and computing the corresponding couplings. , However, one major drawback of such an approach is that the TD-DFT still relies on the short-ranged exchange component of the PBE functional and hence is incapable of fully capturing excitonic effects. To capture such effects, the TD-DFT calculations with hybrid functionals are desirable.…”
mentioning
confidence: 99%